ORIENTATION SYSTEM OF PV PANELS AFTER SUN - GEORGE EDUARD HOLMAN; CIPRIAN AFANASOV (Journal of Engineering Studies and Research)
The purpose of the project is create a PV panels orientation system after the sun, with return to home position when dark is coming. The system must be energetically autonomous, and also have the ability to constantly provide power. The orientation of photovoltaic panels is an important factor that we must take into account in the design of energy production systems based on solar radiation. Solar guidance systems increase the efficiency of the power generation system by keeping the panels in a position perpendicular to the light rays. The two-axis orientation method was used. The wiring diagram has been designed so that the guidance system works in both manual and automatic modes. For the system to be energy-independent and, linked to the power supply of the drive motors for the two axis, we used a MPPT charger for the battery used as a energy source. Finding the best solutions for increasing system efficiency and energy independence will be presented in this paper.